2018
DOI: 10.1001/jamaophthalmol.2018.1621
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction in Patients WithCNGB1-Associated Retinitis Pigmentosa

Abstract: etinitis pigmentosa (RP) (OMIM 26800) is a genetically heterogeneous disease characterized by poor night vision and loss of peripheral visual field owing to a decline in rod-dependent vision. Later in the disease course, cones and thus the central visual field and visual acuity may also be affected. Retinitis pigmentosa is caused by mutations in genes coding for proteins involved in photoreceptor function, structure, and/or maintenance. When the gene product is expressed exclusively in the retina or when its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…The variant c.2492 + 1 G > A has been associated with anosmia patients with arRP due to compound heterozygous mutations in CNGB1 (19). Here we tested extended family members who were carriers of a single CNGB1 mutation (c.2957A>T or c.2492 + 1 G > A) with the SIT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The variant c.2492 + 1 G > A has been associated with anosmia patients with arRP due to compound heterozygous mutations in CNGB1 (19). Here we tested extended family members who were carriers of a single CNGB1 mutation (c.2957A>T or c.2492 + 1 G > A) with the SIT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patient E1, who had a homozygous mutation, c.1431 C > A (p.Cys477*) is expected to be normosmic since the mutation would not be expressed in olfactory neurons. On the other hand, Issa et al (19) reported that a patient with a homozygous mutation, c.1312 C > T (p.(Gln438*) had hyposmia that was borderline high. This is curious since the spliced transcript expressed in the nasal sensory neurons would translate a normal CNGB1a protein subunit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 A subsequent quantitative study found objectively reduced olfactory function in 8 of 9 patients tested (89%), with 3 patients (33%) aware of their olfactory impairment. 3 Variants can occur in the N-terminal glutamic acid-rich protein (GARP) domain or in the channel domain. The GARP domain is important in rod photoreceptors, but its role in olfactory neurons is less clear; an alternatively spliced variant (CNGB1b), lacking this domain, is expressed in olfactory neurons in rats.…”
mentioning
confidence: 99%